Pentingnya Meningkatkan Pengaruh Kemampuan Komunikasi Matematis dan Faktor yang Mempengaruhi Kemampuan Komunikasi Matematis Siswa - Fadya Safitri Rahman; Rora Rizki Wandini (STIKes Ibnu Sina Ajibarang, 2024)
Students’ ability to communicate their mathematical ideas in various ways is not as expected. It is difficult for teachers to improve students’ mathematical communication skills by improving learning styles, improving the learning atmosphere, and using appropriate learning models. Therefore, it is important to know the factors that influence students’ mathematical communication abilities. The aim of this research is to describe the factors that influence students’ mathematical communication skills. The subjects of this research were four children aged approximately 11 years who live in Hamparan Perak District. The data collection techniques used were observation and interviews. Data were analyzed using a qualitative approach. The results of the research show that the factors that influence students’ oral communication skills are study partners, self-confidence, shyness, nervousness, group learning atmosphere, learning time, and gender. Factors that influence students’ written communication skills include the inability to write down known information and be asked about it, lack of concentration in studying and inability to understand the content, as well as question difficulty, which includes the level of composure and composure in solving questions.